Transient Evoked and Distortion Product Otoacoustic Emission Comparison in Children - Dhiaa Mohammed Yaseen; Qasim Ali Khalaf; Haider Kadhem Saeed (Indonesian Journal on Health Science and Medicine, 2026)
General Background Otoacoustic emissions objectively evaluate outer hair cell function in pediatric populations. Specific Background Transient evoked and distortion product paradigms are widely used to assess cochlear responsiveness in pediatric hearing screening. Knowledge Gap Comparative evaluations of signal-to-noise ratio performance across matching frequencies, alongside ear asymmetry and gender dynamics in six-year-olds, remain limited. Aims This study compared screening pass rates, signal-to-noise ratios, and ear or gender variations between both emission paradigms in normal-hearing children. Results Among 130 children (260 ears), both paradigms showed identical 100% pass rates, though distortion product emissions yielded significantly higher signal-to-noise ratios at 2, 3, and 4 kHz ($p < 0.001$), with mostly nonsignificant ear side and gender variations. Novelty This work establishes normative baseline comparative parameters in six-year-olds, proving distortion product signal superiority at identical frequencies. Implications Superior distortion product signal strength provides a clinically advantageous paradigm for pediatric auditory assessment, particularly in noisy environments.   Keywords: Transient Evoked Otoacoustic Emissions, Distortion Product Otoacoustic Emissions, Pediatric Hearing Screening, Signal to Noise Ratio, Cochlear Function   Key Findings Highlights Both emission paradigms achieved equivalent hundred percent screening pass rates among healthy six-year-old pupils. Signal-to-noise ratios were significantly greater in distortion product measurements across identical testing frequencies. Gender and ear side variations remained absent across most frequencies, establishing baseline pediatric normative parameters.